Pengembangan Flipbook Berbasis Gamifikasi sebagai Buku Pendamping IPAS Materi Keragaman Budaya Indonesia Kelas IV SD/MI - Asnafiyah; Rahmaisna Hanum Muffida (Al-Mudarris, 2026)
The limited availability of supplementary learning resources and the underutilization of interactive digital media have constrained the effectiveness of IPAS learning on Indonesian cultural diversity among fourth-grade Madrasah Ibtidaiyah students. Previous studies have demonstrated the effectiveness of flipbooks and gamification in enhancing student engagement; however, research integrating both approaches into a supplementary learning resource specifically designed for cultural diversity content in Madrasah Ibtidaiyah remains limited. This study aimed to develop and evaluate a gamification-based flipbook as a supplementary learning resource for IPAS and to examine students’ responses toward its implementation. The study employed a Research and Development (R&D) approach using the Thiagarajan 4D model, consisting of the define, design, develop, and disseminate stages. Data were collected through expert validation instruments, teacher assessments, and student response questionnaires, and were analyzed using descriptive qualitative and quantitative techniques. The findings revealed that the developed flipbook was highly feasible, obtaining validation scores of 92% from media experts, 77.6% from content experts, and 89% from teachers. Furthermore, student responses reached 82.1%, categorized as “Very Good,” indicating high levels of engagement, usability, and acceptance. The novelty of this study lies in the integration of gamification elements within a flipbook-based supplementary resource specifically designed for Indonesian cultural diversity learning in Madrasah Ibtidaiyah. The study contributes to the development of interactive learning media that not only support conceptual understanding of cultural diversity but also promote student engagement and multicultural awareness in elementary Islamic education contexts.